Analysis Of Labour Inspectors’ Temporary Incapacity For Work - Petya Georeva; Tanya Kuneva; Kiril Karamfiloff; Jivka Stoykova (Journal of Biomedical & Clinical Research, 2015)
It is known that increased morbidity with temporary incapacity for work (MTIW) is related to stress level and psychosocial factors at work. Practices for stress management, conflict avoidance and optimization of working conditions are known to reduce MTIW level. The aim of the present study was to analyze MTIW and propose measures to optimize and reduce strain at work. The study covered MTIW in labour inspectors, a total of 334 people, men and women aged from 24 to 69. The evaluation was based on 11 of the generally accepted indices. MTIW structure was analyzed. MTIW was rated as high according to case frequency and as very high according to day frequency. The average duration of a TI case was 12.63, and the relative share of people who were frequently taken ill for a long period was 12.81. In the ITI structure, diseases of the respiratory system (42.0%) ranked first, followed by diseases of the nervous system (18.8%), the digestive system (9.9%), CVS (8.3%) and MSS (7.2%). These 5 groups of diseases covered 86.2% of all diagnoses. The remaining 7 groups of diseases covered less than 14% of the diagnoses. The group of people most frequently taken ill for long periods included 28 inspectors who had used 42.5% of the total number of days. Two inspectors with 140 days of absence from work were cases of TI resulting from severe stress and adaptation disorder. Measures were proposed regarding the reduction of strain at work and the risk of stress.